Atypical Infections in Tsunami Survivors - Garzoni, Christian; Emonet, Stéphane; Legout, Laurence; Benedict, Rilliet; Hoffmeyer, Pierre; Bernard, Louis; Garbino, Jorge (Emerging Infectious Disease journal, 2005)
After a tsunami hit Asia in December 2004, 2 survivors had severe infections due to multidrug-resistant and atypical bacteria and rare fungi weeks afterwards. Treating these infections is challenging from a clinical and microbiologic point of view.
Keywords: tsunami; Southeast Asia; infection; dispatch; Thailand; Switzerland